Peluang waralaba sebagai strategi peningkatan distribusi produk (studi pada Kopi Anjis) - Marissa Elsa Safiera; Cecep Safa’atul Barkah; Tetty Herawaty; Lina Auliana (Jurnal Kajian Manajemen dan Wirausaha, 2022)
AbstractThis study aims to determine how the right strategy in maximizing the distribution of Kopi Anjis' products. By using descriptive qualitative methods, conducting interviews and observations of Kopi Anjis and some of its competitors. The data obtained were processed using the Sustainable Competitive Advantage (SCA) analysis method, the Valuable, Rare, Inimitable, Non-Substitutable (VRIN) framework and the Strengths, Weaknesses, Opportunities, Threats (SWOT) analysis. The results of the data processing obtained then became the basis for researchers to conduct content analysis to propose a total distribution optimization strategy. The recommended proposal is to open a franchise opportunity. Keyword : Total Distribution, Marketing Strategies, Franchise.Abstrak :Penelitian ini bertujuan untuk mengetahui bagaimana strategi yang tepat dalam memaksimalkan distribusi produk milik Kopi Anjis. Dengan menggunakan metode kualitatif deskriptif, melakukan wawancara serta observasi terhadap Kopi Anjis serta beberapa pesaingnya. Data yang diperoleh diolah dengan menggunakan metode analisis Sustainable Competitive Advantage (SCA), framework Valuable, Rare, Inimitable, Non-Substitutable (VRIN) serta analisis Strengths, Weaknesses, Opportunities, Threats (SWOT). Hasil olah data yang didapat kemudian menjadi dasar peneliti melakukan analisis konten untuk mengusulkan strategi optimalisasi total distribution. Usulan yang dianjurkan adalah dengan membuka peluang waralaba. Kata kunci : Total Distribusi, Strategi Pemasaran, Waralaba.